Recombinant maltose-inducible porin LamB of Aeromonas hydrophila induces TH2-biased mixed immune response and generates cross-species agglutinating antibodies in the murine model - Tanuja Upadhyaya; Sunita Kumari Yadav; Vibhuti Sharma; Puneet Kumar Gupta; Aparna Dixit (Molecular Biology Reports, 2026)

Engineering Amorphous Lipid Nanomaterials for Enhanced Delivery and Anticancer Performance of Lapatinib - Dinanath Gaikwad; Sandip Bandgar; Tanuja Kulkarni; Pratidnya Kodag; Anilkumar Shinde; Dipak Mali (Journal of Pharmaceutical Innovation, 2026)

The structural units, recognition factors (RFs) and their codes of a lFuc Recognition Protein (FRP)+ - Albert M. Wu; Tanuja Singh; Jia Hau Liu; Yung Liang Chen (Glycoconjugate Journal, 2026)

Galgal peel (Citrus pseudolimon): Processing technologies, value addition, and functional food applications–a review - Suhail Ahmad Bhat; Renu Sharma; Usman Ahmed; Tanuja Srivastava; D.C. Saxena (Food Bioscience, 2026)

Phytochemical profiling of different stem extracts of Cissus quadrangularis Linn. as a natural source of resveratrol through TLC, HPTLC & NMR spectroscopy - Arvind Kumar; Tanuja; Vinay Bhushan Kumar (Next Research, 2026)

In-depth analysis of nutritional, antioxidant, anti-nutritional, thermal, spectral and micro-structural properties of value-added extruded snacks - Renu Sharma; Suhail Ahmad Bhat; Tanuja Srivastava; D.C. Saxena (Journal of Cereal Science, 2026)

Understanding charge storage in Li2V6O13 nanobelts through integrated structural, electrochemical and first-principles analysis - Tanuja N. Shinde; Snehal S. Shinde; Amol S. Vedpathak; Bhalchandra S. Pujari; Shrikrishna D. Sartale (Chemical Engineering Journal, 2026)

Integration of Novel Apical Rooted Cutting Technology into Potato Breeder Seed Production - Tanuja Buckseth; Jagesh K. Tiwari; Rajesh K. Singh; A. K. Singh; C. Challam; V. Kumar; Ashwani K. Sharma; Sumita Sharma; M. Sadawarti; Nandh Kumar N.; B. Singh (Potato Research, 2026)

Correction: Tandem mass spectrometry based study on the dissipation behaviour, dietary risk assessment and decontamination of chlorfenapyr, fenvalerate, and tolfenpyrad residues in broccoli - Sapna Katna; Preeti Bansal; Ajay Sharma; Tanuja Banshtu; Nisha Devi; Arvind Kumar; Shubhra Singh; Sakshi Sharma; Ankur Tomar (Environmental Geochemistry and Health, 2026)

Mushroom by-products as ingredients for food applications: A review of health and sustainability benefits - Tanuja Bisht; Pradeep Singh Negi (Food and Humanity, 2026)

Molecular docking insights and comparative GC-MS analysis of fresh and dried Hedychium spicatum Buch.-Ham. essential oils with a focus on antioxidant activity - Aabha Gangwar; Geeta Tewari; Chitra Pande; Om Prakash; Lalit M. Tewari; Tanuja Kabdal; Manisha Joshi (Biochemical Systematics and Ecology, 2026)

Tandem mass spectrometry based study on the dissipation behaviour, dietary risk assessment and decontamination of chlorfenapyr, fenvalerate, and tolfenpyrad residues in broccoli - Sapna Katna; Preeti Bansal; Ajay Sharma; Tanuja Banshtu; Nisha Devi; Arvind Kumar; Shubhra Singh; Sakshi Sharma; Ankur Tomar (Environmental Geochemistry and Health, 2026)

Transcriptomics Reveals Genes Involved in Purple Tuber Colour Development in Potato - Jagesh Kumar Tiwari; Satish Kumar Luthra; Rasna Zinta; Pinky Raigond; Dalamu Dalamu; Tanuja Buckseth (Agricultural Research, 2026)

Augmenting Seed Potato Production Through Integration of Aeroponics, Apical Rooted Cuttings and Sprout Cutting Techniques: A Comprehensive Review - Murlidhar J. Sadawarti; S. P. Singh; Tanuja Buckseth; Vinod Kumar; Rajesh K. Singh; Ashwani K. Sharma; Subhash Katare; Pooja Jatav; Deepanshi Deora; Priyadarshani Khambalkar; R. K. Samadhiya; Brajesh singh (Agricultural Research, 2026)

Antioxidant, antibacterial and antibiofilm activities of Pittosporum napaulense (DC.) against drug-resistant Staphylococcus aureus and Shigella sp - Sajna Sameekshya Hota; Dibya Ranjan Sahoo; Subhaswaraj Pattnaik; Monika Mishra; Tapasa Mishra; Tanuja Sahu; Baishali Basundhara Naik; Malayamarutham Kalyankumarraju; Amit Kumar Dixit; Deepak Lamba; Sanjaya Kumar Y. R.; Rabinarayan Acharya; et al. (Natural Product Research, 2026)

Prodrug-based drug delivery systems: strategic approaches and emerging challenges in targeted therapeutics - Priyanka Chaturvedi; Reena Sharma; Smita Khare; Tanuja Singh; Deepa Shrivastava; Anjali Singh; Jayant Sarolia (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

First report on seasonal variations in chemical composition and pesticidal activities of Alpinia nigra rhizome essential oil - Shailja Singh; Om Prakash; Ravendra Kumar; Tanuja Kabdal; Stuti Arya; Shiv Kumar Dubey; Dharmendra Singh Rawat; Satya Kumar (Biochemical Systematics and Ecology, 2025)

Exploring microalgae-based biodiesel as an alternative fuel: Development, production techniques and environmental impacts - Sakshi Chaudhary; Kaniz Shahar Bano; Tanuja Mohanty; Anjali Kumari; Mohammad Murtaza Mehdi (Biomass and Bioenergy, 2025)

Exploring residue profiles and risk assessment of azoxystrobin and chlorothalonil in peas (Pisum sativum L.) - Sapna Katna; Tanuja Banshtu; Shubhra Singh; Nisha Devi; Arvind Kumar; Sakshi Sharma (Environmental Geochemistry and Health, 2025)

Microplastics assessment in the lower stretch of the Ganga River sediment from East Indian region: Influence of land use and rainfall patterns - Varsha; Rajeev Ranjan; Avinash Dass; Sushil Kumar Singh; Tanuja Singh (Chemosphere, 2025)

In Vivo Seed Potato Production Possibilities Through Sprouts - Tanuja Buckseth; M. J. Sadawarti; Pooja Jatav; Rajesh K. Singh; Jagesh K. Tiwari; Vinod Kumar; Ashwani K. Sharma; Subhash Katare; S. P. Singh; Brajesh Singh (Potato Research, 2025)

Dissipation pattern, risk assessment and decontamination of residues of emamectin benzoate, fipronil and acetamiprid on bell pepper - Arzoo Bakshi; Ajay Sharma; Sapna Katna; Tanuja Banshtu; Nisha Devi; Arvind Kumar; Shubhra Singh; Sakshi Sharma; Pankaj Istatu Sharma; Ankur Tomar; Muskan Baltoo (Environmental Geochemistry and Health, 2025)

Techno-economic assessment of bio-based pyruvate production from rice straw: A commercial viability analysis - Manish Pant; Tanuja Pant (Biomass and Bioenergy, 2025)

Alkaloids as neuroprotectors: targeting signaling pathways in neurodegenerative diseases - Biswajit Kumar Utpal; Md Al Amin; Mehrukh Zehravi; Sherouk Hussein Sweilam; Uppuluri Varuna Naga Venkata Arjun; Y. Bala Madhuri; Jeetendra Kumar Gupta; Lavanya Yaidikar; Tanuja Tummala; R. Suseela; Akiladevi Durairaj; Konatham Teja Kumar Reddy; et al. (Molecular and Cellular Biochemistry, 2025)

Climatic shifts in the Beas Basin: A spatio-temporal analysis of time series of temperature and precipitation of TerraClimate dataset - Tanuja; Rajesh Kumar (Science of The Total Environment, 2025)

Impact of green synthesized iron oxide nanoparticles from Rhododendron arboretum on wheat (Triticum aestivum): Evaluation of morpho-physiological, biochemical and yield attributes - Atul Singh; Tanuja Rawat; Oddem Govardhan; Chhavi Sharma; Pushpa Lohani; Anuj Kumar; Shabir Hassan; Hemant Singh; Sundip Kumar; Raju Ratan Yadav; Sneh Gautam (Biocatalysis and Agricultural Biotechnology, 2025)

Decadal variation in the diatom community structure of a Himalayan river - Tanuja Bartwal; Prakash Nautiyal (Environmental Monitoring and Assessment, 2025)

Enhancing Kodo millet starch-based hybrid gel for fat replacement in cookies: Dual modification (heat treatment-octenyl succinic anhydride) for improved properties - Ritesh Kurichh; Yogesh Kumar; Yograj Bist; Vijay Singh Sharanagat; Tanuja Srivastava; D.C. Saxena (Food Chemistry, 2025)

Novel Rapid In Vitro Method for Screening of Potato Genotypes Against Streptomyces sp. - Chandan Maharana; Vinay Sagar; Sanjeev Sharma; Tanuja Buckseth; Aarti Bairwa; Kailash Naga; Vinod Kumar; Brajesh Singh (Potato Research, 2025)

Dissipation kinetics, safety evaluation and decontamination of residues of the combi-formulation emamectin benzoate 1.50% + fipronil 3.50% SC in/on chilli - Muskan Baltoo; Tanuja Banshtu; Sapna Katna; Ajay Sharma; Sakshi Sharma; Arzoo Bakshi; Siddhant Thakur (Environmental Geochemistry and Health, 2025)

Superhydrophobic northern tooth-like ZnO nanosheets on stainless steel mesh for oil-water separation - Tanuja A. Ekunde; Pradip P. Gaikwad; Rajaram S. Sutar; Shrutika S. Kshirsagar; Rutuja A. Ekunde; Arvind M. Yelpale; Xuesong Huang; Viswanathan S. Saji; Shanhu Liu; Sanjay S. Latthe (Journal of Water Process Engineering, 2025)

Novel Intermediate ATXN10 Alleles in the Healthy Peruvian Population: A Matter of Indigenous American Ethnic Origin - Karina Milla-Neyra; Ismael Araujo-Aliaga; Carla Manrique-Enciso; Elison Sarapura-Castro; Maryenela Illanes-Manrique; Diego Veliz-Otani; Ana Saldarriaga-Mayo; Angel Medina-Colque; Julia Rios-Pinto; Ivan Cornejo-Herrera; Andrea Rivera-Valdivia; Ignacio F. Mata; et al. (The Cerebellum, 2025)

Flupyradifurone application: A promising approach to curtail tomato leaf curl New Delhi virus (ToLCNDV) transmission vectored by Bemisia tabaci in potato farming - Nitish Modgill; Kailash Chandra Naga; Dnyaneshwar Madhukar Firake; Rahul Kumar Tiwari; Subhash Shivaramu; Ravinder Kumar; Anuj Bhatnagar; Tanuja Buckseth; Aarti Bairwa; Chandan Maharana; Sanjeev Sharma; Brajesh Singh (Crop Protection, 2025)

“Effect of total phenol on the control of leafminer ( Phytomyza horticola ) infestation in Pea plants” - Gunjali Dengta; Tanuja Banshtu; Subhash Chander Verma; Neha Gautam; Priyanka Sharma (Natural Product Research, 2024)

Diploid inbred-based hybrids: fast-forward breeding approach in potatoes - Salej Sood; Vikas Mangal; Ajay Kumar Thakur; Tanuja Buckseth; Babita Chaudhary; Vinod Kumar; Brajesh Singh (Physiology and Molecular Biology of Plants, 2024)

Transgenic tobacco plants overexpressing a wheat salt stress root protein (TaSSRP) exhibit enhanced tolerance to heat stress - Mawuli K. Azameti; N. Tanuja; Satish Kumar; Maniraj Rathinam; Abdul-Wahab M. Imoro; P. K. Singh; Kishor Gaikwad; Rohini Sreevathsa; Monika Dalal; Ajay Arora; Vandna Rai; Jasdeep C. Padaria (Molecular Biology Reports, 2024)

Plant Sources Identify Variations in Potato Production Potential Under Aeroponics - Tanuja Buckseth; Sumita Sharma; Jagesh K. Tiwari; V. Kumar; Ashwani K. Sharma; C. Challam; M. Sadawarti; Rajesh K. Singh (Potato Research, 2024)

Phenotypic and transcriptomics characterization uncovers genes underlying tuber yield traits and gene expression marker development in potato under aeroponics - Rasna Zinta; Jagesh Kumar Tiwari; Tanuja Buckseth; Umesh Goutam; Rajesh Kumar Singh; Ajay Kumar Thakur; Shwetank Singh; Vinod Kumar; Manoj Kumar (Planta, 2024)

Dissipation kinetics and the evaluation of dietary risks associated with deltamethrin, ethion, fenazaquin, and fenpropathrin on bell pepper (Solanum annuum L.) - Shubhra Singh; Jatiender Kumar Dubey; Sapna Katna; Ajay Sharma; Tanuja Banshtu; Nisha Devi; Gaganpreet Singh Brar; Gagandeep Singh; Arvind Kumar; Himani Gautam (Environmental Geochemistry and Health, 2024)

The impact of varying glucosinolate and phenolic levels in different genotypes of cauliflower on the larval population of Pieris brassicae - Tanuja Banshtu; Siddhant Thakur; Subhash Chander Verma; Gunjali Dengta; Neha Gautam; Sapna Katna (International Journal of Tropical Insect Science, 2024)

The impact of soil salinity on the chemical properties of soil at Hatiya Upazila, a remote area of Noakhali, Bangladesh - Sujit Kumar Roy; Trisna Das; Tanuja Barua; Md. Arif Chowdhury; Swapan Talukdar; Javed Mallick; Atiqur Rahman; Naif Mana Almakayeel (Journal of Coastal Conservation, 2024)

Elucidating the phosphoregulatory network of predominant phosphosite in AXL kinase: an integrative bioinformatic approach - Levin John; Mejo George; Leona Dcunha; Mahammad Nisar; Diya Sanjeev; Priyanka Pahal; Athira Perunelly Gopalakrishnan; Prathik Basthikoppa Shivamurthy; Sourav Sreelan; Tanuja Yandigeri; Saptami Kanekar; Rajesh Raju; et al. (Journal of Proteins and Proteomics, 2024)

Exploring the phospho-landscape of NEK6 kinase: systematic annotation of phosphosites and their implications as biomarkers in carcinogenesis - Diya Sanjeev; Spoorthi Mendon; Mejo George; Levin John; Athira Perunelly Gopalakrishnan; Mahammad Nisar; Ahmad Rafi; Pahal Priyanka; Tanuja Yandigeri; Rajesh Raju; Saptami Kanekar; Rex Devasahayam Arokia Balaya (Journal of Proteins and Proteomics, 2024)

Transcriptome Analysis Reveals Molecular Signatures Associated with Apical Rooted Cutting (ARC) Technology in Seed Potato Production - Tanuja Buckseth; Jagesh Kumar Tiwari; Rajesh K. Singh; Akhilesh K. Singh; Clarissa Challam; Rasna Zinta; Sumita Sharma; Ashwani K. Sharma; Murlidhar Sadawarti; Manoj Kumar; Vinod Kumar (Journal of Plant Growth Regulation, 2024)

Transcriptome profiling and characterization of genes associated with tuberization under high temperature in aeroponics in potato cv. Kufri Anand - Rasna Zinta; Jagesh Kumar Tiwari; Tanuja Buckseth; Umesh Goutam; Rajesh Kumar Singh; Vinod Kumar; Ajay Kumar Thakur (Genes & Genomics, 2024)

Delineation of groundwater potential zone using geospatial tools and analytical hierarchy process (AHP) in the state of Uttarakhand, India - Atar Singh; Rajesh Kumar; Ramesh Kumar; Prity Singh Pippal; Payal Sharma; Tanuja; Abhilasha Sharma (Advances in Space Research, 2024)

Development of pH-sensitive films based on buckwheat starch, critic acid and rose petal extract for active food packaging - Diksha Thakur; Yogesh Kumar; Vijay Singh Sharanagat; Tanuja Srivastava; D.C. Saxena (Sustainable Chemistry and Pharmacy, 2023)

Biodegradation of di-2-ethylhexyl phthalate by Bacillus firmus MP04 strain: parametric optimization using full factorial design - Madhavi Rashmi; Tanuja Singh; Nitesh Singh Rajput; Shweta Kulshreshtha (Biodegradation, 2023)

First report of Colletotrichum siamense associated with anthracnose on beach spider lily (Hymenocallis littoralis) in India - T.Tharana Poonacha; Farooq khan; Gutha Venkata Ramesh; S. Tanuja; M.L. Supriya; K.B. Palanna (Crop Protection, 2023)

Functional diversity and behavioral changes of microbial communities under salt affected soils - Madhu Choudhary; Hanuman S. Jat; Raj Mukhopadhyay; Manish Kakraliya; Tanuja Poonia; Anshul Phogat; Bharti Dixit; Rakesh Kumar; Sanjay Arora; R.K. Yadav; S.L. Krishnamurthy; Parbodh C. Sharma (Applied Soil Ecology, 2023)

GIS-based morphometric analysis with emphasis on hypsometric appraisal for sub-watershed prioritization: a case study of the Shyamari River Basin, Central India - Prinsi Singh; Kuldeep Prakash; Anjanay Kumar; Ajeet Kumar Kannaujiya; Akash Deep; Tanuja Mohanty (Sustainable Water Resources Management, 2023)

Impact of leading Indo‐Pacific climatic modes in modulating the wave power variability and their trends in the North Indian Ocean - Samiksha S. Volvaiker; Tanuja Nigam; Srinivas Gangiredla (International Journal of Climatology, 2023)
The present study analyses the trend and variability in wave parameters (wave height and wave period) and wave power (WP) in the North Indian Ocean (NIO). The impact of climatic modes such as El‐Niño Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) on the WP of NIO has been investigated using the European Centre for Medium‐Range Weather Forecasts reanalysis datasets (ERA5) for the period 1959–2021. It is observed that along the west coast of India (WCI), the coastal WP increased from south to north during summer whereas, in winter and other seasons the WP increased from north to south. Instead, along the east coast of India (ECI), WP is higher on the north than the south, always. The annual WP climatology along the Indian coasts reveals that WP potential is higher along/adjacent to WCI than the ECI. It was observed that the total significant wave height (SWH) WP anomalies during normal and positive IOD (pIOD) events are mainly dominated by swell WP, whereas during El Niño and combined ENSO‐IOD events, dominated by wind seas. During the peak of pure El‐Niño, the SWH WP shows a basin‐wide increase in WP anomalies. However, during summer, SWH WP showed increasing trends over Bay of Bengal. It is evident from the composite analysis that annual averaged WP anomalies are decreasing in normal, pure pIOD and combined events, but El‐Niño is found to increase the WP anomalies over the Arabian Sea in the region north of 20°N. The present study advocates that a detailed analysis of WP along the Indian coastal regions is beneficial to the renewable energy industries to utilize this as an important energy resource.

Facies and genetic elements within the Late Miocene Middle Siwalik of the Himalayan foreland basin, India: A response of fan-building processes - Tanuja Deopa; U.K. Shukla; Bijendra Pathak (Sedimentary Geology, 2023)

Phytochemical composition, in vitro bioactivity evaluation and in silico molecular docking study of fruit essential oils of Zanthoxylum armatum DC collected from Himalayan region of Uttarakhand, India - Tanuja Kabdal; Himani Karakoti; Pringal Upadhyay; Ravendra Kumar; Om Prakash; Anamika Dhami; Mamta Latwal; Ganesh Pandey; R.M. Srivastava; Satya Kumar; D.S. Rawat (Journal of Asia-Pacific Entomology, 2023)

Identification of bicyclic compounds that act as dual inhibitors of Bcl-2 and Mcl-1 - Abhay Uthale; Aarti Anantram; Prasad Sulkshane; Mariam Degani; Tanuja Teni (Molecular Diversity, 2023)

First report on essential oil composition and biological activities of five Strobilanthes species from Kumaun Region of Uttarakhand, India - Pringal Upadhyay; Sonu Kumar Mahawer; Ravendra Kumar; Om Prakash; Himani Karakoti; Tanuja Kabdal; Dharamendra Singh Rawat (Biochemical Systematics and Ecology, 2023)

Correlation of Body Mass Index with Anthropometric and Biochemical Parameters Among Polycystic Ovary Syndrome Phenotypes - Tanuja Mehra; Sonali Sharma; Tasneem Zahra; Sapna Jangir; Barkha Gupta (Indian Journal of Clinical Biochemistry, 2023)

Hydropower development in the Himalaya: identifying critical river stretches - Tanuja Bartwal; Prakash Nautiyal (Environmental Science and Pollution Research, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Nutritional, Processing and Sensorial Attributes of Organic and Inorganic Indian Potatoes - Pinky Raigond; Sanjay Rawal; Vandana Parmar; Asha Thakur; Bandana; Tanuja Mishra; Som Dutt; Arvind Jaiswal; Milan Kumar Lal; Sushil S. Changan; Dharmendra Kumar; Brajesh Singh (Potato Research, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Computational investigation of drug bank compounds against 3C-like protease (3CLpro) of SARS-CoV-2 using deep learning and molecular dynamics simulation - Tushar Joshi; Priyanka Sharma; Shalini Mathpal; Tanuja Joshi; Priyanka Maiti; Mahesha Nand; Veena Pande; Subhash Chandra (Molecular Diversity, 2022)

Influence of Micro-plant Hardening Methods on Aeroponic Potato Mini-tuber Production - Tanuja Buckseth; Rajesh K. Singh; Jagesh K. Tiwari; Sumita Sharma; Anuja Gautam; Ashwani K. Sharma; M. J. Sadawarti; Manoj Kumar (Potato Research, 2022)

A glance at the chemodiversity of Ocimum species: Trends, implications, and strategies for the quality and yield improvement of essential oil - Tanuja P. Gurav; Bhushan B. Dholakia; Ashok P. Giri (Phytochemistry Reviews, 2022)

Using Chou’s 5-steps rule to study pharmacophore-based virtual screening of SARS-CoV-2 Mpro inhibitors - Hemlata Pundir; Tanuja Joshi; Tushar Joshi; Priyanka Sharma; Shalini Mathpal; Subhash Chandra; Sushma Tamta (Molecular Diversity, 2021)

Structure-based screening of novel lichen compounds against SARS Coronavirus main protease (Mpro) as potentials inhibitors of COVID-19 - Tanuja Joshi; Priyanka Sharma; Tushar Joshi; Hemlata Pundir; Shalini Mathpal; Subhash Chandra (Molecular Diversity, 2021)

On the interaction of mesoscale eddies and a tropical cyclone in the Bay of Bengal - Kumar Ravi Prakash; Tanuja Nigam; Vimlesh Pant; Navin Chandra (Natural Hazards, 2021)

Recent Updates on Healthy Phytoconstituents in Potato: a Nutritional Depository - Tanuja Mishra; Pinky Raigond; Nitasha Thakur; Som Dutt; Brajesh Singh (Potato Research, 2020)

Conservation Agriculture-based Sustainable Intensification of Cereal Systems Leads to Energy Conservation, Higher Productivity and Farm Profitability - H. S. Jat; K. M. Choudhary; D. P. Nandal; A. K. Yadav; Tanuja Poonia; Yadvinder Singh; P. C. Sharma; M. L. Jat (Environmental Management, 2020)

Chitosan: a Safe Alternative to Synthetic Fungicides to Manage Dry Rot in Stored Potatoes - Pinky Raigond; Vinay Sagar; Tanuja Mishra; Asha Thakur; Brajesh Singh; Vinod Kumar; Vijai Kishor Gupta; Som Dutt; Sushil Sudhakar Changan (Potato Research, 2019)

Influence of Photoperiod and EDTA Salts on Endogenous Gibberellic Acid Concentration of Tissue Culture Grown Potato Microplants - Pinky Raigond; Tanuja Buckseth; Brajesh Singh; Bhawana Kaundal; Rajesh Kumar Singh; Bir Pal Singh (Agricultural Research, 2019)

Impact of Indian ocean dipole on the coastal upwelling features off the southwest coast of India - Tanuja Nigam; Vimlesh Pant; Kumar Ravi Prakash (Ocean Dynamics, 2018)

Effect of Seasons on Subsequent Production Behavior of Small Size Potato Mini-tubers - Ashwani K. Sharma; Tanuja Buckseth; R. K. Singh (Agricultural Research, 2018)

Estimation of oceanic subsurface mixing under a severe cyclonic storm using a coupled atmosphere–ocean–wave model - Kumar Ravi Prakash; Tanuja Nigam; Vimlesh Pant (Ocean Science, 2018)
A coupled atmosphere–ocean–wave model was used to examine mixing in the upper-oceanic layers under the influence of a very severe cyclonic storm Phailin over the Bay of Bengal (BoB) during 10–14 October 2013. The coupled model was found to improve the sea surface temperature over the uncoupled model. Model simulations highlight the prominent role of cyclone-induced near-inertial oscillations in subsurface mixing up to the thermocline depth. The inertial mixing introduced by the cyclone played a central role in the deepening of the thermocline and mixed layer depth by 40 and 15 m, respectively. For the first time over the BoB, a detailed analysis of inertial oscillation kinetic energy generation, propagation, and dissipation was carried out using an atmosphere–ocean–wave coupled model during a cyclone. A quantitative estimate of kinetic energy in the oceanic water column, its propagation, and its dissipation mechanisms were explained using the coupled atmosphere–ocean–wave model. The large shear generated by the inertial oscillations was found to overcome the stratification and initiate mixing at the base of the mixed layer. Greater mixing was found at the depths where the eddy kinetic diffusivity was large. The baroclinic current, holding a larger fraction of kinetic energy than the barotropic current, weakened rapidly after the passage of the cyclone. The shear induced by inertial oscillations was found to decrease rapidly with increasing depth below the thermocline. The dampening of the mixing process below the thermocline was explained through the enhanced dissipation rate of turbulent kinetic energy upon approaching the thermocline layer. The wave–current interaction and nonlinear wave–wave interaction were found to affect the process of downward mixing and cause the dissipation of inertial oscillations.

Petrotectonic setting of the provenance of Lower Siwalik sandstones of the Himalayan foreland basin, southeastern Kumaun Himalaya, India - Pradeep K. Goswami; Tanuja Deopa (Island Arc, 2018)
Detailed petrography and modal analysis of 35 sandstone thin sections was carried out to determine petrotectonic setting of the provenance of the Lower Siwalik molasse of southeastern Kumaun Himalaya. The sandstones are fine‐ to coarse‐grained (0.14–0.63 mm), poorly‐ to moderately‐sorted and comprise lithic arenites, sublithic arenites and lithic greywackes. The sandstones invariably belong to the quartzolithic QtFL (Qt, total quartz; F, feldspar; L, lithic grains) and QmFLt (Qm, monocrystalline quartz; Lt, lithic grains plus polycrystalline quartz) petrofacies, and indicate their derivation from a quartzose‐ and transitional‐recycled orogen provenance under sub‐humid climatic conditions. The framework composition of the sandstones comprises abundant monocrystalline and polycrystalline quartz and low‐ to high‐grade metamorphic rock fragments, along with subordinate feldspar, characterized by low ratios of plagioclase to total feldspar, and accessory minerals. The framework composition and petrofacies characters of these texturally submature sandstones suggest their derivation mainly from the nearby located Great Himalaya terrane and subordinately from the Tethys and Lesser Himalayan terranes. A comparison of the data presented here with the previous similar data from Lower Siwalik of northwestern Pakistan, northwestern India, south‐central Kumaun, western Nepal and southeastern Nepal reveals that like the Lower Siwalik rivers in other sections, the Lower Siwalik rivers of the southeastern Kumaun too drained large parts of the Great Himalayan terrane and some parts of the Tethys and Lesser Himalayan terranes.

Identification of new resistant sources for bacterial blight in pomegranate - B. Tanuja Priya; B. N. S. Murthy; C. Gopalakrishnan; Rashmi B. Artal; S. Jagannath (European Journal of Plant Pathology, 2016)

Water repellent effects of manure amended soils on organic matter decomposition, C retention, and respired CO2-C - Dewpura A. L. Leelamanie; Tanuja D. P. Liyanage (Biologia, 2016)

Peripheral nerve axons contain machinery for co-translational secretion of axonally-generated proteins - Tanuja Merianda; Jeffery Twiss (Neuroscience Bulletin, 2013)

Geochemistry of the suspended sediment in the estuaries of the Mandovi and Zuari rivers, central west coast of India - Pratima M. Kessarkar; R. Shynu; V. Purnachandra Rao; Feng Chong; Tanuja Narvekar; Jing Zhang (Environmental Monitoring and Assessment, 2013)

The influence of tuberculosis treatment on efavirenz clearance in patients co-infected with HIV and tuberculosis - Tanuja N. Gengiah; Nicholas H. G. Holford; Julia H. Botha; Andrew L. Gray; Kogieleum Naidoo; Salim S. Abdool Karim (European Journal of Clinical Pharmacology, 2012)

IL-23 in Infections, Inflammation, Autoimmunity and Cancer: Possible Role in HIV-1 and AIDS - Govardhana Rao Yannam; Tanuja Gutti; Larisa Y. Poluektova (Journal of Neuroimmune Pharmacology, 2012)

Molecular cloning, sequence analysis and structure modeling of OmpR, the response regulator of Aeromonas hydrophila - Gagan Chhabra; Tanuja Upadhyaya; Aparna Dixit (Molecular Biology Reports, 2012)

Expression of recombinant Apple chlorotic leaf spot virus coat protein in heterologous system: production and use in immunodiagnosis - Tanuja Rana; Vanita Chandel; Vipin Hallan; Aijaz A. Zaidi (Journal of Plant Biochemistry and Biotechnology, 2011)

Effect of various surfactants (cationic, anionic and non-ionic) on the growth of Aspergillus parasiticus (NRRL 2999) in relation to aflatoxin production - Kosuri Tanuja; K. Hemalatha; Rupula Karuna; B. Sashidhar Rao (Mycotoxin Research, 2010)

Analysis of the Coat Protein Gene of Indian Strain of Apple Stem Grooving Virus - Anuradha Negi; Tanuja Rana; Yogesh Kumar; Raja Ram; Vipin Hallan; Aijaz A. Zaidi (Journal of Plant Biochemistry and Biotechnology, 2010)

Molecular characterization of the Indian strain of Apple mosaic virus isolated from apple (Malus domestica) - Tombisana Thokchom; Tanuja Rana; Vipin Hallan; Raja Ram; Aijaz A. Zaidi (Phytoparasitica, 2009)

Molecular characterization and variability analysis of Apple scar skin viroid in India - Yashika Walia; Yogesh Kumar; Tanuja Rana; Pooja Bhardwaj; Raja Ram; Pritam Das Thakur; Usha Sharma; Vipin Hallan; A. A. Zaidi (Journal of General Plant Pathology, 2009)

Type 2 diabetes mellitus: phylogenetic motifs for predicting protein functional sites - Ashok Sharma; Tanuja Rastogi; Meenakshi Bhartiya; A. K. Shasany; S. P. S. Khanuja (Journal of Biosciences, 2007)

Molecular analysis of the rstR and orfU genes of the CTX prophages integrated in the small chromosomes of environmental Vibrio cholerae non‐O1, non‐O139 strains - Tanuja Bhattacharya; Souvik Chatterjee; Diganta Maiti; Rupak K. Bhadra; Yoshifumi Takeda; G. Balakrish Nair; Ranjan K. Nandy (Environmental Microbiology, 2006)
Summary The ctxAB genes encoding cholera toxin, reside in the genome of a filamentous bacteriophage CTXφ. The presence of CTX prophage in non‐epidemic environmental Vibrio cholerae strains is rare. The CTX prophage, the lysogenic form of CTXφ in V. cholerae , is comprised of the ‘RS2’ and the ‘Core’. Analysis of the rstR gene present in the RS2 region of the CTX prophage revealed the presence of new alleles of the prophages in four environmental non‐O1, non‐O139 strains VCE22 (O36), VCE228 (O27), VCE232 (O4) and VCE233 (O27), and the CTX prophages are located in the small chromosomes. Phylogenetic analysis based on the nucleotide sequences of the rstR and orfU (present in the core) genes of these prophages placed them in a single unique cluster, which is distally located compared with that of epidemic V. cholerae O1 strains. Further analysis indicated that the genome of the prophage present in the strain VCE22 is devoid of the ctxAB genes, called pre‐CTX prophage and the strain also possess the toxin‐coregulated pilus protein coding gene tcpA of classical type, another important pathogenicity determining locus of the epidemic V. cholerae strains. Comparative analysis of the nucleotide sequences of the rstR and orfU genes indicated that the pre‐CTX prophage of VCE22 might be the progenitor of new alleles of the CTX prophages present in these environmental strains.

Hydrophobicity and surface electrostatic charge of conidia of the mycoparasitic Trichoderma species - Tanuja Singh; Ratul Saikia; Tarakanta Jana; Dilip K. Arora (Mycological Progress, 2004)

Incipient sexual isolation in thenasuta-albomicans complex ofDrosophila: mating preference in male-, female- and multiple-choice mating experiments - M. T. Tanuja; N. B. Ramachandra; H. A. Ranganath (Journal of Biosciences, 2001)

Incipient sexual isolation in thenasuta-albomicans complex ofDrosophila: No-choice experiments - M. T. Tanuja; N. B. Ramachandra; H. A. Ranganath (Journal of Biosciences, 2001)

Evolution of a new chromosomal lineage in a laboratory population ofDrosophila through centric fission - M. T. Tanuja; N. B. Ramachandra; H. A. Ranganath (Journal of Biosciences, 1999)

Evolution of a recent neo-Y sex chromosome in a laboratory population ofDrosophila - M. T. Tanuja; N. B. Ramachandra; H. A. Ranganath (Journal of Genetics, 1999)